A IMPORTÂNCIA DOS PRECEDENTES: UMA ANÁLISE DO CONSTITUCIONALISMO E DO EFEITO BACKLASH NO SISTEMA CONSTITUCIONAL BRASILEIRO - LEITE, YASMIN REIS DE SOUZA (2024)
The study aims to examine the role of judicial precedents in the Brazilian constitutional system, highlighting their importance in ensuring legal certainty and the challenges posed by the backlash effect. This concept is understood as an adverse reaction to judicial decisions, which can hinder the implementation of progressive measures and generate legal instability. The research focuses on the tension between the application of precedents, innovative decisions, and the negative reactions they provoke, especially on sensitive issues. The study discusses the evolution of constitutionalism in Brazil and the role of the Supreme Federal Court in constitutional review, proposing strategies to mitigate the backlash effect, such as promoting institutional dialogue and adopting well-founded decisions. The conclusion points to the relevance of judicial precedents as a fundamental tool to ensure equality and predictability in decisions, promoting stability and legal certainty. The proper use of precedents is considered crucial for the efficiency of the judiciary and to avoid contradictory decisions that could fuel social backlash.